PENGARUH GENDER, PENGALAMAN AUDIT DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT - Y. Sunyoto; Dedy Christiyanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The importance of audit judgment is to give an opinion about the fairness of financial reports based on financial accounting standards or general accounting principles and the standard application consistently. This study aims to determine the effect of gender, auditor experience and task complexity on audit judgment at Public Accounting Firms in Indonesia. This study uses a survey method which uses primary data obtained from questionnaires. The population in this study is Public Accountants and Auditors who work at Public Accounting Firms in Indonesia. The number of samples in this study is 100 respondents who are taken with a convenience sampling technique. The data analysis technique in this study uses multiple regression test. Finally, the results showed that the variables of gender, audit experience and task complexity, partially (t test) has a positive and significant effect on audit judgment.